Reconstruction Of The Arrangements For The Appointment Of Advocates - Kamaluddin, Moh; Sarbini, Sarbini; Lusiana, Wyda (Universitas Negeri Gorontalo, 2022)
The quality of advocates is currently in decline. This is due to the absence of similarity of standardization between advocate organizations. In addition, there are also many prospective advocates who have an internship certificate even though they have never done a 2-year internship but are still appointed as advocates. The formulation of the problem in this article is to analyze; (1) Weaknesses of the Advocate Appointment Arrangements in article 2 and article 3 of Law Number 18 of 2003 concerning Advocates and (2) The ideal construction of Advocate Appointment Arrangements in article 2 and article 3 of Law Number 18 of 2003 concerning Advocates. This research uses a conceptual approach with data collection techniques using interviews or filling out questionnaires and for secondary data derived from literature or legal documents then analyzed in a descriptive analysis . The result of the discussion The process of appointing advocates regulated in article 2 and article 3 of the advocate law has weaknesses; There is no obligation of the advocate organization to check the validity in the advocate appointment file, There are commercialization factors in the process of appointing advocates, There is no special institution that guarantees the standardization of the quality of advocates, therefore to overcome these problems it is necessary to regulate the Authority of the Advocate Organization to re-verifying the documents of the Appointment of Advocates, The unity of the system of the cost of appointment of advocates, The establishment of standardization institutions with advocates.